Quality of life and pain relief in men with metastatic castration‐resistant prostate cancer on cabazitaxel: the non‐interventional 'QoLiTime' study. (30th September 2016) - Hofheinz, Ralf‐Dieter; Lange, Carsten; Ecke, Thorsten; Kloss, Susanne; Linsse, Burkhard; Windemuth‐Kieselbach, Christine; Hammerer, Peter; Al‐Batran, Salah‐Eddin
Abstract : Objective: To examine health‐related quality of life (QoL) in men with metastatic castration‐resistant prostate cancer (mCRPC) on cabazitaxel. Patients and Methods: Men with mCRPC receiving cabazitaxel (25 mg/m², every 3 weeks) and 10 mg/day oral prednis(ol)one were enrolled (2011–2014) in the non‐interventional prospective 'QoLiTime' study. Primary outcome was change in QoL (European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire 30‐item) with respect to prostate‐specific antigen (PSA) response after four cycles of cabazitaxel. Secondary outcomes included occurrence of adverse events (AEs). Results: Of 527 men, 348 received four cycles of cabazitaxel and 266 had the necessary PSA level measurements. After four cycles, 92 (34.6%) men had a PSA level decrease ≥50% (responders). QoL remained stable throughout the study ( P = 0.62). Change in QoL did not differ between responders and non‐responders ( P = 0.69). Change in PSA level and global health status between baseline and four cycles showed an inversely proportional relationship (correlation coefficient –0.14; 95% confidence interval –0.26 to –0.01; P = 0.03), with increasing PSA level corresponding to lower health status. Responders showed no change in physical functioning vs baseline (–1.75, P = 0.12); non‐responders showed a reduction vs baseline (–7.00, P < 0.001) and responders ( P = 0.05). Responders showed an improvement in pain vs baseline (–7.61, P = 0.05) and vs non‐responders ( P = 0.01). AEs occurred in 292 patients (55.4%), most commonly anaemia (16.5%), fatigue (12.3%) and diarrhoea (11.8%). Neutropenia and febrile neutropenia were reported in 3.8% and 3.6% of patients, respectively. Conclusion: Prostate‐specific antigen level response was associated with stable physical functioning and improvement in pain. Symptom increases were seen in areas typical of chemotoxicity, but QoL was maintained.